Investigation of Electrochemical Oxidation of Methanol at a Carbon Paste Electrode Modified with Ni(II)‐BS Complex and Reduced Graphene Oxide Nano Sheets. Issue 12 (19th July 2016) - Mousavi, Zeinab; Benvidi, Ali; Jahanbani, Shahriar; Mazloum‐Ardakani, Mohammad; Vafazadeh, Rasoul; Zare, Hamid R.
Abstract: In the present research, the electro oxidation of methanol was investigated by different electrochemical methods at a carbon paste electrode (CPE) modified with bis(salicylaldehyde)‐nickel(II)‐dihydrate complex (Ni(II)‐BS) and reduced graphene oxide (RGO) (which named Ni(II)‐BS/RGO/CPE) in an alkaline solution. This modified electrode showed very efficient activity for oxidation of methanol. It was found that methanol was oxidized by NiOOH groups generated by further electrochemical oxidation of nickel (II) hydroxide on the surface of the modified electrode. The rate constant and electron transfer coefficient were calculated to be 2.18 s −1 and 0.4, respectively. The anodic peak currents revealed a linear dependency with the square root of scan rate. This behaviour is the characteristic of a diffusion controlled process, so the diffusion coefficient of methanol was found to be 1.16×10 −5 cm 2 s −1 and the number of transferred electron was calculated to be 1. Moreover, differential pulse voltammetry (DPV) investigations showed that the peak current values were proportional to the concentration of methanol in two linear ranges. The obtained linear ranges were from 0.5 to 100.0 µM (R 2 =0.991) and 400.0 to 1300.0 µM (R 2 =0.992), and the detection limit was found to be 0.19 µM for methanol determination. Generally, the Ni(II)‐BS/RGO/CPE sensor was used for determination of methanol in an industrial ethanol solution containing 4.0 % methanol. Abstract :